NOTARY'S LIABILITY FOR TYPICAL ERRORS IN THE COPY OF THE DEED THAT HAS BEEN ISSUED - Anthony Astrawinata; Gerwyn Andrea; Rahmaniar Novita Mas; Vindy Kusuma (Jurnal Ilmiah Advokasi, 2024)
Notaries have a very important role in making authentic deeds that have permanent legal force. Authentic deeds made by notaries are made based on requests from parties who have interests. In making an authentic deed, a notary must apply the principle of caution. Typical errors made by the notary can result in the deed being drawn up. Errors that can occur in a deed are insubstantial errors and substantial errors. The case at issue is a deed that has been read in front of the presenters and has been signed by the presenters. A copy of the deed has been issued and given to the presenters, but it turns out there is an error in the minutes of the deed. The problem is what the notary's efforts are to correct errors in the deed whose copy has been issued to the presenters and what is the notary's responsibility where the consequences of the minute deed are errors due to his negligence and a copy is issued to the presenters. The research method used is normative research, which is carried out by examining library materials. Efforts that can be made by the Notary are to issue a copy of the correct deed and make an official report stating that the incorrect copy of the deed has been justified, which will become the Notary's archive. Minutes are issued if the copy has been given to a third party. In this case, the applicant can sue the notary for compensation. Notaries may be subject to civil sanctions and administrative sanctions.Keywords: Notary, Accountability, Copy of Deed